Ludoterapia como técnica psicoterapéutica para disminuir conductas agresivas en niños de educación básica regular de la escuela católica Dr. José Jaramillo Montoya del periodo 2014 - 2015. - Ramírez Campoverde, Mayra del Rocío (2015)
The play therapy is a psychotherapeutic method based on the use of the game as a means able to make the individual learns to understand himself better , is helpful in the case of children with behavioral therapy is based on the game of useful , as the play their natural means of self expression , the child has the opportunity to act in this way all their accumulated feelings of tension, frustration , insecurity, fear.